Recent developments in the synthesis of N-aryl sulfonamides. Issue 15 (3rd August 2021) - Wu, Huizhen; Chen, Xuesong; Sun, Nabo; Sanchez-Mendoza, Alberto
Abstract: The construction of N-aryl sulfonamides is usually an important reaction in organic synthesis because these compounds are privileged in the structure of many natural products and pharmaceutical molecules. Also, N-aryl sulfonamides are well-known due to their antibacterial, antitumor, and anti-HIV biological activities. Therefore, research on the laboratory synthesis of N-aryl sulfonamides is an important challenge in organic synthesis. In this review, we discussed on methods reported up to now for the synthesis of N-aryl sulfonamides with the goal of stimulating further progresses in this field. We believe that this review will open up a new road for the preparation of pharmaceutically and biologically active sulfonamides. Graphical Abstract: UF0001